2015
DOI: 10.1186/s12870-015-0637-8
|View full text |Cite
|
Sign up to set email alerts
|

Proline affects the size of the root meristematic zone in Arabidopsis

Abstract: BackgroundWe reported previously that root elongation in Arabidopsis is promoted by exogenous proline, raising the possibility that this amino acid may modulate root growth.ResultsTo evaluate this hypothesis we used a combination of genetic, pharmacological and molecular analyses, and showed that proline specifically affects root growth by modulating the size of the root meristem. The effects of proline on meristem size are parallel to, and independent from, hormonal pathways, and do not involve the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 53 publications
(84 reference statements)
4
38
0
3
Order By: Relevance
“…Of different amino acids in roots, maximum increase was noted in proline level upon Sar and Jan applications, which clearly indicated that proline, apart from its well established function as stress-protectant 41 , is also a key contributor for improving growth. The growth enhancement effect of proline is mainly due to its role in regulating G2/M-specific CYCLINB1;1 gene expression and providing hydroxyproline-rich glycoproteins that serve as structural constituents of cell wall 42 , 43 . Surprisingly, even under control conditions, enzymatic antioxidant activities were increased, resulting in decreased H 2 O 2 and MDA contents in Sar- and Jan-treated plants, as compared with that in WS plants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Of different amino acids in roots, maximum increase was noted in proline level upon Sar and Jan applications, which clearly indicated that proline, apart from its well established function as stress-protectant 41 , is also a key contributor for improving growth. The growth enhancement effect of proline is mainly due to its role in regulating G2/M-specific CYCLINB1;1 gene expression and providing hydroxyproline-rich glycoproteins that serve as structural constituents of cell wall 42 , 43 . Surprisingly, even under control conditions, enzymatic antioxidant activities were increased, resulting in decreased H 2 O 2 and MDA contents in Sar- and Jan-treated plants, as compared with that in WS plants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Research using amino acid or ureide transporter mutants or overexpressors has demonstrated that modifications in organic N transport processes and associated alterations in symplasmic, subcellular or apoplastic N pools induce complex physiological changes in source and sink. The signals inducing these changes are still unknown but might involve specific amino acids such as glutamine/glutamate (Gutierez et al ., ) and proline (Wang et al ., ; Biancucci et al ., ), or related N compounds such as S‐methyl‐methionine or allantoin (Tan et al ., ; Nourimand & Todd, ; Takagi et al ., ). In addition, changes in the C : N ratio (Wang & Ruan, ), amino acid imbalance (Liu et al ., ; Yu et al ., ) or other factors including mRNAs, small RNAs, peptides, proteins and hormones (Lee et al ., ; Bellegarde et al ., ) may present signals causing plant responses via complex transduction pathways.…”
Section: Regulation Of Nitrogen Transportmentioning
confidence: 99%
“…For instance, it is involved in osmotic stress management and accumulates as important osmolyte during stress conditions [38] and as a result of dehydration [39]. Accumulation of proline can be a result of incompatible plant microbe interactions [40] and can enhance the root growth by increasing the root meristematic zone [41]. Similarly, AMF are known to be triggering increased root growth [42].…”
Section: Discussionmentioning
confidence: 99%